2023
DOI: 10.1097/md.0000000000036069
|View full text |Cite
|
Sign up to set email alerts
|

Does bore size matter?—A comparison of the subjective perception of patient comfort during low field (0.55 Tesla) and standard (1.5 Tesla) MRI imaging

Arwed Elias Michael,
Andreas Heuser,
Christoph Moenninghoff
et al.

Abstract: The purpose of the present study was to evaluate the subjectively perceived patient comfort during magnetic resonance imaging (MRI) examinations and to assess potential differences between a recently introduced low field MRI scanner and a standard MRI scanner. Among other characteristics, the low field MRI scanner differs from the standard MRI scanner by offering more space (wider bore size of 80 centimeter diameter) and producing less noise, which may influence the patient comfort. In total, 177 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, to apply it to humans, technical and scientific issues, such as understanding the impact of strong magnetic fields on humans, developing biocompatible SPIO, and enlarging the equipment, must be resolved [ 20 , 23 ]. Among these, the development of equipment with a bore size large enough for a person to enter (regular: 50–60 cm, wide: 80 cm, based on MRI) is a very important issue [ 24 ], as it must be used in preclinical experiments and tests, such as the development and safety confirmation of SPIO for humans. Based on the papers and presentations published to date, it has been reported that the usual bore sizes of MPI range from 3 cm to 20 cm [ 1 , 14 , 20 ], and thus far, MPI at a level suitable for small animals is common [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to apply it to humans, technical and scientific issues, such as understanding the impact of strong magnetic fields on humans, developing biocompatible SPIO, and enlarging the equipment, must be resolved [ 20 , 23 ]. Among these, the development of equipment with a bore size large enough for a person to enter (regular: 50–60 cm, wide: 80 cm, based on MRI) is a very important issue [ 24 ], as it must be used in preclinical experiments and tests, such as the development and safety confirmation of SPIO for humans. Based on the papers and presentations published to date, it has been reported that the usual bore sizes of MPI range from 3 cm to 20 cm [ 1 , 14 , 20 ], and thus far, MPI at a level suitable for small animals is common [ 25 ].…”
Section: Discussionmentioning
confidence: 99%